Reflection of the change process in enhancing organizational performance (Analytical research) - فائق تلا عاصم; عبد عذراء محسن (Journal of Economics and Administrative Sciences, 2018)
This research aims to test the relation and effect of the process of organizational change as an independent variable (change in human resources, technological change, change in tasks, change in organizational structure) in organizational performance as a variable of success (financial performance, operational performance, customer satisfaction, growth). And learning) in the Office of the province of Baghdad, as well as determine the existence of differences of statistical significance between the variables of research, and then try to come out with a set of recommendations to contribute to the strengthening of organizational performance, and carried out this research on the eye of the vertical number (75) individuals, The questionnaire was used as a main tool for collecting data on the research variables through the measurements that were constructed. In addition, the interview was used as well as some paper data. In order to process the data and information, the Statistical Analysis Program (SPSS) The results were obtained by means of several statistical methods (the percentages and frequencies, the analysis of averages, the standard deviation, correlation analysis, linear regression analysis, the coefficient of variation, and the Kay square test). The main hypothesis was accepted (there is a statistically significant correlation between the exclusion of organizational change and organizational performance). There is also a relationship between organizational change and organizational performance. The hypothesis was accepted Second, there is a statistically significant effect on the exclusion of organizational change in organizational performance. The research ended with a number of conclusions. Technological change and change in tasks are the most important dimensions that are directly related to the development of organizational performance. Knulogi and change in the tasks represent the most prominent and most influential dimensions of performance.